2010
DOI: 10.4319/lo.2010.55.5.1965
|View full text |Cite
|
Sign up to set email alerts
|

Grazer‐induced defence in Phaeocystis globosa (Prymnesiophyceae): Influence of different nutrient conditions

Abstract: We examined the combined effects of grazer infochemicals and nutrient status on colony development of Phaeocystis globosa cultures grown under nitrogen and phosphorus (NP)-sufficient, P-deficient, and N-deficient conditions exposed to high and low Acartia spp. density filtrates. Changes in colony development relative to controls receiving no grazer signals were estimated. P. globosa colony development responded to grazer infochemicals regardless of nutrient status, although the expression of the response varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
17
2
Order By: Relevance
“…Because pH was not measured in the present study in the flasks that contained the copepods and because of the obviously complex mechanisms by which it may affect DA production, we cannot totally exclude the possibility that pH, at least in part, had an impact on the DA levels. Long et al (2007) and Lundgren and Granéli (2010) found no differences in pH between the grazing treatments (A. tonsa and P. globosa) and controls (only P. globosa). In other similar induction experiments with copepodites and P. seriata, no significant changes in pH were found (N. Lundholm unpubl.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because pH was not measured in the present study in the flasks that contained the copepods and because of the obviously complex mechanisms by which it may affect DA production, we cannot totally exclude the possibility that pH, at least in part, had an impact on the DA levels. Long et al (2007) and Lundgren and Granéli (2010) found no differences in pH between the grazing treatments (A. tonsa and P. globosa) and controls (only P. globosa). In other similar induction experiments with copepodites and P. seriata, no significant changes in pH were found (N. Lundholm unpubl.).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assume that factors other than nutrients caused the increase in DA production. Levels of major inorganic nutrients have been measured in only a few studies, which have shown that chemicals released by the zooplankton induced either physiological or morphological responses in phytoplankton (Selander et al, 2006;Long et al, 2007;Lundgren and Granéli, 2010); however, the nutrients themselves have not been found to be the inductive factor in these studies. Selander et al (2006) assumed that the possible effect of excretions (ammonium) from A. tonsa to be negligible at saturating nutrient conditions in comparison to the effect of chemical cues from A. tonsa in enhancing PST production A. minutum.…”
Section: Discussionmentioning
confidence: 99%
“…Induced defenses would therefore be favored over constitutive ones in environments with variable predatory pressure (Tollrian and Harvell, 1999). Some studies have now observed changes in both the morphology (Hessen and Van Donk, 1993;Long et al, 2007;Lundgren and Grané li, 2010) and the toxin production (Jang et al, 2003;Selander et al, 2006;Bergqvist et al, 2008) of various phytoplankton. Such responses may reduce vulnerability to grazing (Hessen and Van Donk, 1993;Selander et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports on Scrippsiella trochoidea temporary cyst induction in response to various detrimental chemical signals (Fistarol et al 2004, Toth et al 2004, Tillmann et al 2007, Tillmann & Hansen 2009 (Selander et al 2006) and to induce morphological changes in Phaeocystis globosa (Long et al 2007, Lundgren & Granéli 2010) via released infochemicals. Although the studies cited above imply that S. trochoidea could be able to respond to infochemicals released from A. tonsa, the present study showed that this was not the case.…”
Section: Effects Of Acartia Tonsa Exposurementioning
confidence: 99%
“…By adjusting the timing of recruitment from the 'seed-bank', these algae could avoid being grazed (Hansson 1996. Some phytoplankton species are also able to respond to infochemicals released by zooplankton by adjusting other defensive traits, such as morphology (Hessen & van Donk 1993, Tang 2003, Lundgren & Granéli 2010 and toxin production (Jang et al 2003, Selander et al 2006, and thus these species become less vulnerable to grazing (Hessen & van Donk 1993, Selander et al 2006.…”
Section: Introductionmentioning
confidence: 99%